From the Biology of PP2A to the PADs for Therapy of Hematologic Malignancies - Ciccone, Maria; Calin, George A.; Perrotti, Danilo (Frontiers in Oncology, 2015)
Over the past decades, an emerging role of phosphates in the pathogenesis of hematologic malignancies and solid tumors has been established. The tumor suppressor Protein phosphatase 2A (PP2A) belongs to the serine-threonine phosphatases family and accounts for the majority of serine-threonine phosphatase activity in eukaryotic cells. Numerous studies have shown that inhibition of PP2A expression and/or function contributes to disengage kinases and impairs the balance between kinases and phosphatases activities. Interestingly, in some cases unrestrained oncogene kinases suppresses PP2A activity, thus promoting a feed-back loop which further allows unrestrained kinase activity. Likewise, overexpression or aberrant expression of physiologic PP2A inhibitory molecules (e.g. SET and its associated SETBP1 and CIP2A) may turn off PP2A function and participate to leukemic progression. In chronic myeloid leukemia PP2A down-regulation seems to be a hallmark feature of leukemic hematopoietic progenitor and stem cells. Likewise, PP2A loss-of-function seems to confer poor prognosis also in many other myeloid and lymphoid malignancies. The discovery of PP2A as tumor suppressor has prompted the evaluation of the safety and the efficacy of new compounds which can restore PP2A activity in leukemic cells. Albeit further studies are needed to better understand how PP2A acts in the intricate phosphatases/kinases cancer network, the results reviewed herein strongly support the development on new PP2A activating drugs (PADs) and the immediate introduction of those available into clinical protocols for leukemia patients refractory or resistant to current available therapies.